2020
DOI: 10.3389/fevo.2020.00254
|View full text |Cite|
|
Sign up to set email alerts
|

Plant-Induced Transgenerational Plasticity Affecting Performance but Not Preference in a Polyphagous Moth

Abstract: Environmental variation experienced by a single genotype can induce phenotypic plasticity in various traits, such as behavioural, physiological and developmental characteristics. It can occur within the lifetime of an individual through within-generation phenotypic plasticity (WGP) or vertically across generations through transgenerational phenotypic plasticity (TGP). However, knowledge about TGP and the co-occurrence of WGP and TGP is still limited. In insect host-plant selection, the ability to alter phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…maternal effects, where non-genetic components, such as egg nutrients, are transferred from the mother to her offspring to improve their fitness (Bernardo 1996). However, as the results in our current paper indicate that females do not alter egg size depending on larval host plant species, we suggest that egg size in itself does not explain the mechanism behind the transgenerational effects previously found in S. littoralis (Rösvik et al 2020). Indeed, egg size may not be the only parameter for estimating egg investment and egg quality as the yolk protein content could be unrelated to egg size (Diss et al 1996).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…maternal effects, where non-genetic components, such as egg nutrients, are transferred from the mother to her offspring to improve their fitness (Bernardo 1996). However, as the results in our current paper indicate that females do not alter egg size depending on larval host plant species, we suggest that egg size in itself does not explain the mechanism behind the transgenerational effects previously found in S. littoralis (Rösvik et al 2020). Indeed, egg size may not be the only parameter for estimating egg investment and egg quality as the yolk protein content could be unrelated to egg size (Diss et al 1996).…”
Section: Discussioncontrasting
confidence: 57%
“…There may also be more complex relationships between egg quantity and egg quality in insects than a simple trade off (Fischer et al 2003). Rösvik et al (2020) recently showed indications of transgenerational plasticity on offspring performance in S. littoralis depending on parental host plant species during the larval stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many fundamental questions that are common to both insects and vertebrates remain to be resolved, for example, how the brain integrates early-life experience across multiple levels of organization, and whether specific mechanisms like DNA methylation universally predict long term behavioral impacts. Moreover, it remains unclear how developmental experiences are integrated with other sources of information (e.g., genetic variation, parental transgenerational effects) that also influence behavior (Dall et al, 2015;Stamps and Frankenhuis, 2016;Stein et al, 2018;Rösvik et al, 2020), and whether these outcomes can be modified by additional information later in life. Though these sources of complexity apply to both insect and vertebrate species, certain characteristics of insects, like their relatively short lifespans, may alter the ecological selection pressures that shape information integration.…”
Section: Discussionmentioning
confidence: 99%
“…Spodoptera littoralis feeds on more than 80 different plant species from over 40 different families (CABI, 2019), and the host range thus spans over plants which may be very different in terms of nutrient content and chemical defenses. This species has been shown to be very plastic in terms of host plant preference and performance (Anderson et al, 2013;Lhomme et al, 2018;Proffit et al, 2015;Rösvik et al, 2020;Roy et al, 2016;Thöming et al, 2013), where larval development, fecundity, and mating propensity differ depending on which host plant species they feed on (Rösvik et al, 2020;Karlsson Green et al, 2021). Furthermore, parasitoid success on S. littoralis could differ depending on host plant species, which may result from a combination between increased larval immune defense and variation in parasitoid search behavior depending on plant species (Sadek et al, 2010).…”
mentioning
confidence: 99%